HUBUNGAN PENGUASAAN MATERI MENGAJAR GURU DENGAN PRESTASI BELAJAR SISWA DI MTsN KADUR KECAMATAN KADUR KABUPATEN PAMEKASAN TAHUN 2018 - Abd Haris (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2019)
In general, education can be categorized into two categories, namely the world of formal and non-formal education. While the implementation of education will not be separated from the activities of the teaching and learning process, and in the learning process there are several factors including how the teacher is required to master the subject matter that will be delivered to the students themselves. Subject matter is something that the teacher presents to be processed and then developed by students, in the achievement model of instructional objectives. Based on the discussion of the results of the research conducted by researchers about the relationship of teacher teaching material to student achievement in Kadur MTsN Kadur Pamekasan Regency which consists of two problems, researchers can draw formulas from the discussion presented in front, conclusions that can be drawn from this thesis are as The following: 1) The relationship between mastery of teacher teaching material and student achievement at MTsN Kadur Pamekasan is a very urgent relationship because without a good relationship it is difficult to achieve the desired goals by the teacher and students. 2) With good communication between the teacher and the students, students will be more active in learning, and with good communication will also show a match between what the teacher has to say and the students' abilities.